Antioxidant and Pro-Oxidant Activities of Melatonin in the Presence of Copper and Polyphenols In Vitro and In Vivo - Jiajia Wang; Xiaoxiao Wang; Yufeng He; Lijie Jia; Chung S. Yang; Russel J. Reiter; Jinsong Zhang (Cells, 2019)
Melatonin is a well-documented antioxidant. Physicochemical analysis using the density functional theory suggests that melatonin is a copper chelating agent; however, experimental evidence is still in demand. The present study investigated the influence of melatonin on reactive oxygen species (ROS) generated from polyphenol autoxidation in the presence of copper. Surprisingly, we found that melatonin paradoxically enhanced ROS formation in a redox system containing low concentrations of copper and quercetin (Que) or (−)-epigallocatechin-3-gallate (EGCG), due to reduction of cupric to cuprous ion by melatonin. Addition of DNA to this system inhibited ROS production, because DNA bound to copper and inhibited copper reduction by melatonin. When melatonin was added to a system containing high concentrations of copper and Que or EGCG, it diminished hydroxyl radical formation as expected. Upon addition of DNA to high concentrations of copper and Que, this pro-oxidative system generated ROS and caused DNA damage. The DNA damage was not prevented by typical scavengers of hydroxyl radical DMSO or mannitol. Under these conditions, melatonin or bathocuproine disulfonate (a copper chelator) protected the DNA from damage by chelating copper. When melatonin was administered intraperitoneally to mice, it inhibited hepatotoxicity and DNA damage evoked by EGCG plus diethyldithiocarbamate (a copper ionophore). Overall, the present study demonstrates the pro-oxidant and antioxidant activities of melatonin in the redox system of copper and polyphenols. The pro-oxidant effect is inhibited by the presence of DNA, which prevents copper reduction by melatonin. Interestingly, in-vivo melatonin protects against copper/polyphenol-induced DNA damage probably via acting as a copper-chelating agent rather than a hydroxyl radical scavenger. Melatonin with a dual function of scavenging hydroxyl radical and chelating copper is a more reliable DNA guardian than antioxidants that only have a single function of scavenging hydroxyl radical.